Gait Spatio-Temporal Parameters Vary Significantly Between Indoor, Outdoor and Different Surfaces - Lorenzo Brognara; Alberto Arceri; Marco Zironi; Francesco Traina; Cesare Faldini; Antonio Mazzotti (Sensors)
Human gait is usually studied in clinical environments, but wearable devices have extended gait analysis beyond traditional assessments. Older adults tend to walk differently indoors and outdoors; however, most gait assessments are conducted on indoor surfaces. It is therefore important to evaluate gait in various outdoor environments. Insights gained from these assessments significantly enhance our understanding of the impact of environmental factors on gait performance and ensure that clinical evaluations are effectively aligned with everyday locomotion. A total of 100 participants with foot pain, 38 young (18–45 years) and 62 older adults (65–80 years), completed a 10-Metre Walk Test (10MWT) in three randomised conditions at their typical, comfortable walking pace, including (1) 10MWT of indoor walking, (2) 10MWT of outdoor walking on grass and (3) 10MWT of outdoor walking on a sidewalk. Wearable inertial sensors recorded gait data and the magnitudes of the following gait measures: gait speed, cadence, stride length, stride duration and asymmetry. A statistical analysis using ANOVA and post hoc comparisons revealed a significantly lower gait speed (p < 0.001), lower stride length (p < 0.001) and lower asymmetry (p < 0.001) indoors compared to outdoors, demonstrating that environmental factors significantly affect spatio-temporal gait parameters. Wearable sensor-based gait analysis performed in controlled clinical settings may underestimate real-life conditions. Some important spatio-temporal parameters, useful in detecting people with gait impairment and at risk of falling, are significantly affected by environment and individual postural ability more than demographic factors.